(untitled) (Physical Education, Health and Social Sciences, 2025)
When we use the term story, we specifically mean a "short story," which is referred to in English as a "Short Story.The short story is a product of the modern era. Its emergence is significantly influenced by contemporary complexities and human preoccupations, especially at a time when people had limited time to read due to the demands of daily life and the challenges of modernity. In response to this need, literature developed that was brief yet meaningful, designed to be read in a single sitting. The short story reflects social issues, human emotions, and the spirit of the nation, while maintaining its own artistic style and aesthetic principles distinct from novels or dramas. Key literary features include unity of impression, plot structure, characterization, and conciseness. Its themes can encompass various aspects of human life, such as love, hatred, joy, sorrow, and political, social, or economic realities. The title, introduction, and opening sentence must be engaging to captivate the reader. Overall, the short story is a literary form that presents human emotions, events, and social realities in a concise and impactful manner. A story is an important creative genre; although it often contains fictional elements, these are based on certain truths, through which past events of life and occurrences of the era can be clearly observed. This study follows Qualitative Research principles, using Textual Analysis to examine the technical aspects of modern and traditional stories, Critical Review to assess critics’ views, Comparative Method to contrast stories with novels and dramas, and Thematic Analysis to explore themes, characters, plots, and effects. The research aims to analyze the technical composition of modern short stories, their stylistic features, and the influence of contemporary human experiences. Research Questions: What are the key technical elements of modern short stories? How do contemporary conditions affect style and theme? How do stories differ from novels and dramas? How do social and psychological factors influence theme selection? How do modern stories meet current literary needs? The study concludes that modern short stories are a vital literary form, effectively portraying human life, social conflicts, and emotions in a concise and meaningful way.